Internal Labor Markets: Too Many Theories, Too Few Facts - Baker, George P.; Holmström, Bengt (American Economic Review, 1995)
That firms employ internal labor markets, in which wages and careers are partly shielded from the vagaries of external labor markets, seems well accepted. Yet, Peter Doeringer and Michael Piore's (1985) seminal work on internal labor markets has had a rather limited impact on the economics profession. In contrast to textbooks on human-resource management, which have adopted their paradigm wholeheartedly, labor economics texts tend to pay only cursory attention to internal labor markets. The competitive model, in which wages reflect an individual's marginal product, remains the paradigm of choice. There are many reasons for this lackluster reception, including intellectual convenience. A more acceptable excuse is that while Doeringer and Piore's study, which was based on interviews with 75 companies, identified several key regularities (ports of entry, career ladders, etc.) that have come to shape our perception of internal labor markets, the book never presented a theory to explain these findings. With the advent of information economics and contract theory, models of internal labor markets-or at least selected features of these markets-have begun to emerge. The objective of these theories is to show that internal-labor-market outcomes can be construed as second-best solutions to contracting problems under incomplete information. For instance, tournament theory (Edward Lazear and Sherwin Rosen, 1981) sees the attachment of wages to jobs as part of an efficient incentive scheme. Michael Waldman (1984) explains the same phenomenon as an insurance arrangement against variations in individual productivity. Seniority rules in promotion and wagesetting can be understood as responses to problems of collusion or influence activities (Paul Milgrom and John Roberts, 1988). The list could be extended. At this point, there is hardly any feature of internal labor markets that cannot be given some logical explanation using the right combination of uncertainty, asymmetric information and opportunism. Doeringer and Piore (1985), in the preface to the second printing of their book, take exception with this line of theoretical research. They believe that internal labor markets are inherently a social (group) phenomenon and that something fundamental is missed by pursuing individualistic models. Be that as it may, we think there is another, more serious problem with the direction that this research has taken: too much of it relies on the old empirical stereotype. The original study was done 25 years ago and focused almost exclusively on blue-collar, male, unionized, manufacturing workers. One might rightly wonder how relevant these findings are in today's environment and whether they extend to white-collar work as most discussions seem to assume. Before proceeding with the theory, it is prudent to ask: do we have the facts right? In this paper we report on two recent case studies of individual firms that use personnel records to analyze wage and career paths of managerial workers: Lazear (1992) and Baker et al. (1994a,b).1 Person-